«El puente de los pecadores»: Ethics and corruption in Peruvian constructions - Polo Valerio, William Alexander (2021)
In this article I will analyse the issues of unethical behaviour and corruption that are present in the constructions carried out in our country. To this end, I will focus on the story of «El puente de los pecadores»: a text in which the Mendicant Librarian refers to the corruption in a certain work carried out in the seventeenth century.